Design research : methods and perspectives. - Laurel, Brenda, ....- (Cambridge : MIT, 2003)
The tools of design research, writes Brenda Laurel, will allow designers "to claim and direct the power of their profession." Often neglected in the various curricula of design schools, the new models of design research described in this book help designers to investigate people, form, and process in ways that can make their work more potent and more delightful. "At the very least," Peter Lunenfeld writes in the preface, "design research saves us from reinventing the wheel. At its best, a lively research methodology can reinvigorate the passion that so often fades after designers join the profession." The goal of the book is to introduce designers to the many research tools that can be used to inform design as well as to ideas about how and when to deploy them effectively. The chapter authors come from diverse institutions and enterprises, including Stanford University, MIT, Intel, Maxis, Studio Anybody, Sweden?s HUMlab, and Big Blue Dot. Each has something to say about how designers make themselves better at what they do through research, and illustrates it with real world examples-case studies, anecdotes, and images. Topics of this multi-voice conversation include qualitative and quantitative methods, performance ethnography and design improvisation, trend research, cultural diversity, formal and structural research practice, tactical discussions of design research process, and case studies drawn from areas as unique as computer games, museum information systems, and movies. Interspersed throughout the book are one-page "demos," snapshots of the design research experience. Design Research charts the paths from research methods to research findings to design principles to design results and demonstrates the transformation of theory into a richly satisfying and more reliably successful practice.
Keywords: Ontwerpen